Rapid guide to hazardous chemicals in the environment - Richard P Pohanish (Van Nostrand Reinhold, 1997)
The book covers - in alphabetical order - by the USEPA's regulatory name, approximately 1.500 chemicals and chemical categories that appear in federal and state regulations. The chemicals were taken from 26 different listings, including CAA, CWA, RCRA, SDWA, Comprehensive Environmental Reponse, CERCLA, EPCRA, Marine Pollutants from DOT Hazardous Materials Transportation, and California's Proposition 65 carcinogens and reproductive toxins